Transcriptomic Responses of Salmonella enterica Serovars Enteritidis in Sodium Hypochlorite - Wang, Sheng; Xiao, Xingning; Qiu, Mengjia; Wang, Wensi; Xiao, Yingping; Yang, Hua; Dang, Yali; Wang, Wen (Frontiers in Cellular and Infection Microbiology, 2022)
Salmonella enterica serovars Enteritidis (S. Enteritidis) can survive extreme food processing environments including bactericidal sodium hypochlorite (NaClO) treatments generally recognized as safe. In order to reveal the molecular regulatory mechanisms underlying the phenotypes, the overall regulation of genes at the transcription level in S. Enteritidis after NaClO stimulation were investigated by RNA-sequencing. We identified 1399 differentially expressed genes (DEG) of S. Enteritidis strain CVCC 1806 following treatment in liquid culture with 100 mg/L NaClO for 20 min (915 up-regulated and 484 down-regulated). Analyses of these expression patterns indicated that genes encoding key regulatory factors and effectors responding to membrane damage, membrane transport functions, oxidative stress, DNA repair, virulence factors and biofilm formation were significantly up-regulated. These included outer (sthB, invG, yohG) and inner (ydgK, yddG, emrB) membrane components responding to membrane damage. The outer membrane β-barrel protein ompS was significantly upregulated and performs multiple functions in the outer membrane in response to environmental stressors. Besides, the exocytosis pump-related genes yceE, ydhE, and ydhC are upregulated, which are capable of transporting structurally distinct molecules (including antibiotics) out of bacterial cells. This efflux lowers the intracellular antibiotic concentration, allowing bacteria to survive at higher antibiotic concentrations. Genes encoding the spermine/putrescine ABC (potA, potB, potC) and zinc (znuB, znuC) transporter systems were also significantly up-regulated. upregulation of transporter system genes may lead to enhanced cellular information transduction and accelerated biofilm formation, potentially enhancing bacterial adaptation to extreme environments. Key regulators of oxidative stress (ahpF, dps, soxR) and DNA repair are also significantly upregulated. Genes encoding the major flagellar proteins including the key regulator fis were upregulated. Its upregulation will result in increased flagellar motility, allowing cells to move toward nutrients and retreat from harmful substances. Interestingly, genes related to energy metabolism such as most tricarboxylic acid cycle genes were significantly down-regulated. This most likely decreased the total energy charge of the cells and plays an unknown role in adaptation to NaClO exposure. Therefore, this study indicated that S. Enteritidis has genomic mechanisms to adapt to NaClO stress.